Активные и интерактивные формы проведения занятий при подготовке бакалавров социальной работы - Melnikov S. V. (Modern education development theory techniques and practice, 2016)
efficiency of educational process in many respects depends on technologies of higher education. Article is devoted to the analysis of some technologies, bases, conditions and the principles of their application; the author makes the recommendations submitted on success of application of these innovative technologies of professional education.
Keywords: профессиональное образование; педагогические технологии; professional education; pedagogical technologies; innovation of study; инновационность учебной работы